2015
DOI: 10.1038/onc.2015.133
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-induced EMT promotes targeted migration of breast cancer cells through the lymphatic system by the activation of CCR7/CCL21-mediated chemotaxis

Abstract: Tumor cells frequently disseminate through the lymphatic system during metastatic spread of breast cancer and many other types of cancer. Yet it is not clear how tumor cells make their way into the lymphatic system and how they choose between lymphatic and blood vessels for migration. Here we report that mammary tumor cells undergoing epithelial–mesenchymal transition (EMT) in response to transforming growth factor-β (TGF-β1) become activated for targeted migration through the lymphatic system, similar to dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
193
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(210 citation statements)
references
References 46 publications
7
193
2
3
Order By: Relevance
“…However, it is not clear what drives cancer cells to choose the lymphatic system for migration. Mikael C. Karlsson et al demonstrated that EMT promotes the migration of breast cancer through the lymphatic system to lymph nodes and that HLECs secrete chemokines to attract EMT cells [39,40]. Similar to those results, we found that LNMICC overexpression could induce EMT in cervical cancer cells and activate the expression of VEGF-C to promote lymphangiogenesis via FABP5-mediated reprogramming of FA metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…However, it is not clear what drives cancer cells to choose the lymphatic system for migration. Mikael C. Karlsson et al demonstrated that EMT promotes the migration of breast cancer through the lymphatic system to lymph nodes and that HLECs secrete chemokines to attract EMT cells [39,40]. Similar to those results, we found that LNMICC overexpression could induce EMT in cervical cancer cells and activate the expression of VEGF-C to promote lymphangiogenesis via FABP5-mediated reprogramming of FA metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…Among these 72 candidate genes, genes that control cancer cell stemness (including NF-κB1 [34], IL-1β [35], and CCR7 [36, 37]) and that scored significantly in the screen were selected, thereby demonstrating the effectiveness of the screen. However, genes that control pluripotency (including IL-6, and STAT3 [38]) did not score significantly in the screen possibly reflecting insufficient knockdown, redundancy, or that their role in CSC identity did not involve OCT4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is via both Smad-dependent and -independent pathways including p38 MAPK. P38 MAPK can also be activate by Ras and Wnt which act with TGF-b synergistically, while the Smad pathway is unique to TGF-b signalling [19]. Hepatocyte growth factor plays a crucial role in initiating EMT via both PI3K/Akt pathway and RAF-MEK-ERK pathway [20,21].…”
Section: Background Of Emtmentioning
confidence: 99%